Visual Afterimages of Emotional Faces in High Functioning Autism. - Rutherford, M.; Troubridge, Erin; Walsh, Jennifer (Journal of Autism & Developmental Disorders, 2012)
Fixating an emotional facial expression can create afterimages, such that subsequent faces are seen as having the opposite expression of that fixated. Visual afterimages have been used to map the relationships among emotion categories, and this method was used here to compare ASD and matched control participants. Participants adapted to a facial expression for 45 s then saw a neutral face for 800 ms and chose a label to describe the latter. The ASD group showed evidence of afterimages, but atypical patterns of opposition: whereas fixating negative emotions uniformly evokes a positive afterimage in the control group, fixating negative emotions was more likely to evoke a negative afterimage in the ASD group. This study was the first to provide evidence of visual aftereffects in ASD and suggests a different psychological organization among emotions in those with ASD.